APPROACHES AND STRATEGIES FOR ENHANCING DISCIPLINE AND SOCIAL-EMOTIONAL SKILLS IN STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Hielda Choirun Nisa; Hitta Alfi Muhimma; Ganes Gunansyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This systematic literature review examines evidence-based approaches and strategies for enhancing discipline and social-emotional skills in students across various educational settings. The review synthesizes 28 empirical studies published between 2021 and 2025, encompassing meta-analyses, randomized controlled trials, systematic reviews, and mixed-methods investigations. Key findings reveal that universal social-emotional learning (SEL) programs demonstrate significant positive effects on student competencies, behavioral outcomes, school climate, and academic achievement. Mentalization-based interventions, emotion regulation training, and whole-school approaches show promise in reducing disruptive behavior and fostering prosocial development. Evidence-based classroom management programs and structured SEL curricula emerge as effective strategies for integrating discipline support with competency development. Implementation quality, teacher self-efficacy, family involvement, and autonomy-supportive teaching practices are identified as critical moderating factors. The review highlights persistent challenges including the need for culturally responsive adaptations, longitudinal outcome measurement, and differential effectiveness for students with special educational needs. Recommendations emphasize the importance of tiered support systems combining universal prevention with targeted interventions, professional development focused on implementation fidelity, and systematic monitoring of discipline indicators alongside social-emotional competencies. This review provides educators, policymakers, and researchers with comprehensive guidance for selecting, implementing, and evaluating integrated approaches to discipline and social-emotional learning.